A tourist map of Xi'an: combining historical city characteristics with art. Issue 1 (1st January 2020) - Weng, Min; Song, Xiaoyan; Wang, Lingqi; Xie, Huan; Zhang, Ping; Su, Shiliang; Kang, Mengjun
ABSTRACT: The design of tourist maps of historical cities sometimes fails to balance functionality and artistry or does not fully reflect cities' cultural connotations. In this paper, we select Xi'an, China, as a study case and design a tourist map through a spatial narrative to reflect its artistic characteristics in the layout design, color design and symbol design. A few operational suggestions are proposed for improving functionality and artistry in tourist mapping, including variable scales, topological optimization, hand-painted symbols and colors extracted from the architecture of the city.